We have to find the derivative of y = (sin x + cos x)/(sin x - cos x)

Use the quotient rule that states: if y = f(x)/g(x), y' = [f'(x)g(x) - f(x)g'(x)]/(g(x))^2

y = (sin x + cos x)/(sin x - cos x)

y' = [(cos x - sin x)(sin x - cos x) - (sin x + cos x)(cos x + sin x)]/(sin x - cos x)^2

=> [cos x*sin x - (cos x)^2 - (sin x)^2 + sin x*cos x -sin x*cos x - (cos x)^2 - (sin x)^2 - sin x*cos x]/(sin x - cos x)^2

=> [-2(cos x)^2 - 2(sin x)^2]/(sin x - cos x)^2

**The required derivative is [-2(cos x)^2 -2(sin x)^2]/(sin x - cos x)^2**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now